Study on Combinatorial Algorithm in Linear Model - Jana Izvoltova; Peter Pisca (Advanced Aspects of Engineering Research Vol. 11, 2021)
Gauss-Jacobi combinatorial algorithm is an alternative approach to traditional iterative estimation methods. The combinatorial algorithm is often used for outlier diagnosis in nonlinear models, where the other parameter estimation methods lose their efficiency. The paper describes comparison of both of Gauss-Jacobi and Gauss-Markov models applied on parameter estimation process of levelling network for the reason to find the efficiency of combinatorial algorithm in simply linear model.